Association between fish intake and incidence of sarcopenia in community-dwelling older adults after a 6-year follow-up: the Korean frailty and aging cohort study - Yi, Seunghyun; Kim, Miji; Won, Chang Won; Park, Yongsoon (Frontiers in Nutrition, 2025)
Previous studies have suggested beneficial effects of n-3 polyunsaturated fatty acids on sarcopenia. However, the associations of dietary fish intake with the prevalence of sarcopenia are inconsistent, and those with the incidence of sarcopenia has not been studied. This study investigated the hypothesis that seafood and fish consumption is inversely associated with the subsequent incidence of sarcopenia. Using data from the Korean Frailty and Aging Cohort Study, 503 non-sarcopenic community-dwelling Korean adults aged 70–84 years were followed-up for 6 years. Sarcopenia was defined according to the Asian Working Group for Sarcopenia 2019 consensus. Dietary intake was assessed using two non-consecutive 24-h dietary recalls at baseline. The incidence of sarcopenia was 37.8% after the 6-year follow-up. The intake of oily fish was inversely associated with the incidence of sarcopenia (OR 0.99; 95% CI 0.98–1.00; p for trend = 0.046) and that of low gait speed (OR 0.98; 95% CI 0.97–1.00; p for trend = 0.016) after the 6-year follow-up, adjusting for confounding factors. Consumption of total seafood, fish, non-oily fish, or shellfish was not significantly associated with the incidence of sarcopenia or its parameters, such as muscle mass, handgrip strength, usual gait speed, 5-times sit-to-stand test, or the Short Physical Performance Battery. The findings demonstrate that the consumption of oily fish could be beneficial in preventing sarcopenia, particularly by improving usual gait speed in Korean community-dwelling older adults, suggesting oily fish as a strategy to reduce sarcopenia risk.